Marginal Uncertainties Making a Living and Working on the Outskirts of Milan - Giacomo Pozzi; Luca Rimoldi (EtnoAntropologia)
In this article we question the meanings and social practices related to living and working in the Social Housing neighbourhoods of Milan’s present-day suburbs. Through the reconstruction of several narratives, we shed light on how uncertainty characterises the professional everyday lives of those social actors who play a particularly significant role in Milan’s complex arena of social housing management (social workers; bailiffs; inspectors; “trouble-solvers”). Isolation, neglect and conflict are the main terms used by the social actors, both to describe the ongoing housing precarity of those who are at risk of losing their homes and to frame the current conditions of social housing. These represent crucial interpretative keys for developing a thick understanding of the housing crisis.